Obstructive sleep apnea and 19 gastrointestinal diseases: a Mendelian randomization study - Yan, Weiheng; Zhou, Jiayi; Jiang, Miaomiao; Kong, Yaru; Qin, Han; Qi, Yuwei; Wang, Shan; Tai, Jun (Frontiers in Psychiatry, 2024)
Background: Alterations gastrointestinal diseases (GDs) were reported in individuals with obstructive sleep apnea (OSA), however, the genetic background between OSA and GDs is still unclear.Methods: This investigation employed Mendelian randomization (MR) analyses to evaluate the causal effect between OSA and 19 types of GDs (gastroesophageal reflux disease (GERD), ulcerative colitis, celiac disease, crohn's disease, chronic gastritis, irritable bowel syndrome, primary biliary cholangitis, diverticular disease, gastroduodenal ulcer, acute pancreatitis, non-alcoholic fatty liver disease, primary sclerosing cholangitis, cirrhosis, calculus of bile duct, calculus of gallbladder, pancreatic cancer, gastric cancer, colorectal cancer, and oesophageal cancer). The inverse-variance weighted (IVW) method was used to evaluate the main effects model of causality.Results: This MR study suggests that OSA may play a causal role inflammation-related GDs (GERD, PIVW=5.94×10 -9 ; gastroduodenal ulcer, PIVW=1×10 -4 ; chronic gastritis, PIVW=0.0214; ulcerative colitis, p=0.0296), and gallstones (calculi of the gallbladder, PIVW=0.0429; bile duct, PIVW=0.0068). After accounting for obesity, type 2 diabetes, smoking, and alcohol consumption, the multivariate MR (MVMR) analysis identified that OSA is an independent risk factor for GERD, gastroduodenal ulcer, and calculus of the bile duct. The reverse MVMR analysis showed a causal effect of GERD on OSA. Besides, we did not find that the predisposition to OSA was associated with 4 cancers.This MR analysis provides compelling evidence of an independent causal relationship between genetically predicted OSA and an elevated risk of inflammation-related GDs. Besides, no causal association was observed between OSA and cancers. Further studies should be carried out to verify our findings.